Analysis of rain fade slope for terrestrial links - Jalel Chebil; Al-Hareth Zyoud; Mohamed Hadi Habaebi; Islam Md. Rafiqul; Hassan Dao (Institute of Advanced Engineering and Science, 2020)
Rainfall can cause severe degradation to the operation of microwave links working with frequencies above 10 GHz. Many studies have investigated this problem, and one of the factors that attract the attention of researcher is rain fade slope which is the rate of change of rain attenuation. The focus of this study is on rain fade slope for terrestrial links and it is based on measurement conducted in Malaysia. This paper investigates the characteristics of the measured rain fade slope distribution for various attenuation levels. Then, the ITU-R model for rain fade slope is compared with the corresponding statistics obtained from the measured data. Significant discrepancies have been observed since the ITU-R prediction model does not fit the measured fade slope distribution for many attenuation levels. It is recommended to modify the expression of the standard deviation in the ITU-R model when implemented in tropical regions.